Factors Affecting Consumers’ Intentions to Use Online Food Delivery Services During COVID-19 Outbreak in Jabodetabek Area - Rano Kartono; Jane Kartika Tjahjadi (Bina Nusantara University, 2021)
The research intended to scrutinize aspects affecting intentions to use online food delivery services during COVID-19 outbreak in Jabodetabek area. The research applied Theory of Reasoned Action (TRA) that integrated perceived trustworthiness, perceived relative advantage, perceived risk and attitude toward using to give insights on factors affecting consumers’ intention when using online food delivery services. Data collection was conducted by quantitative, non-probability, purposive sampling methods. The research instrument was online questionnaires that were spread out to all people who had experienced using online food delivery services at least once, during COVID-19 outbreak (Feb-May 2020). In total, there were 127 valid returned questionnaires used to analyze data variables using PLS-SEM method through SMART-PLS 2.0 M3 software. The results find out that perceived trustworthiness, perceived relative advantage, and perceived risk positively affect consumers’ attitudes toward using online food delivery service. Perceived trustworthiness and attitude toward using positively affects intention to use online food delivery services. However, perceived risk negatively affects intention to use online food delivery services during COVID-19 outbreak in Jabodetabek area.